2017
DOI: 10.1002/dac.3359
|View full text |Cite
|
Sign up to set email alerts
|

Maximum harvested energy policy in full‐duplex relaying networks with SWIPT

Abstract: Summary It is considered that energy scavenging is a promising way for source node transfer energy to powered constraint relay in cooperative networks with advantage of cost‐effective maintenance and flexible deployment, which so‐called simultaneous wireless information and power transfer. In this paper, relay selection for optimal wireless energy is investigated. In terms of time switching–based relaying, this paper considers the performance comparison of 3 proposed relay selection schemes, namely, (1) optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Following the principle of energy harvesting [14][15][16][17][18][19], the harvested power is given by…”
Section: A First Phase: Energy Harvestingmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the principle of energy harvesting [14][15][16][17][18][19], the harvested power is given by…”
Section: A First Phase: Energy Harvestingmentioning
confidence: 99%
“…In this section, the outage probability is main metric considered in our proposed model. The outage performance is defined in many works [14][15][16][17]. We now consider outage probability for such NOMA transmission as below.…”
Section: Outage Performance Analysis In Scheme Imentioning
confidence: 99%
“…Additionally, advantages of relaying networks can be implemented together with NOMA to reform hybrid scheme, namely, cooperative NOMA, in which relay serves far user with improved performance by assigning signal processing techniques including decode and forward or amplify and forward modes. In particular, a dedicated half‐duplex relay in the traditional dual‐hop cooperative relaying system to serve NOMA users .…”
Section: Introductionmentioning
confidence: 99%
“…The key idea in NOMA showed that multiple users are served in the same time slot/subcarrier/spreading code. It is shown that both energy and information can be transmitted by RF signals together, from the same received RF signals; Nguyen and Do 10 have put forward the simultaneous wireless information and power transfer (SWIPT). 2 Several parameters such as user pairing and power allocation algorithms are presented in downlink of NOMA.…”
Section: Introductionmentioning
confidence: 99%
“…The radio frequency (RF) signals in the ambient wireless have emerge as a reliable energy source apart from natural ones like vibration, wave, and solar. It is shown that both energy and information can be transmitted by RF signals together, from the same received RF signals; Nguyen and Do 10 have put forward the simultaneous wireless information and power transfer (SWIPT). A wireless power transfer is proposed as a promising EH technology in which users harvest energy from electromagnetic radiation.…”
Section: Introductionmentioning
confidence: 99%